2007
DOI: 10.1073/pnas.0706292104
|View full text |Cite
|
Sign up to set email alerts
|

ATPase activity of KaiC determines the basic timing for circadian clock of cyanobacteria

Abstract: Self-sustainable oscillation of KaiC phosphorylation has been reconstituted in vitro, demonstrating that this cycle is the basic time generator of the circadian clock of cyanobacteria. Here we show that the ATPase activity of KaiC satisfies the characteristics of the circadian oscillation, the period length, and the temperature compensation. KaiC possesses extremely weak but stable ATPase activity (15 molecules of ATP per day), and the addition of KaiA and KaiB makes the activity oscillate with a circadian per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
417
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 244 publications
(452 citation statements)
references
References 19 publications
34
417
1
Order By: Relevance
“…Terauchi et al (5) show that the ATPase activity of KaiC is only slightly affected by temperature (Q 10 Ϸ 1.2) in mixtures with KaiA and KaiB, which is consistent with the in vivo rhythm in cyanobacterial gene expression. Interestingly, the ATPase activity of KaiC when incubated without KaiA and KaiB is almost constant across temperatures.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Terauchi et al (5) show that the ATPase activity of KaiC is only slightly affected by temperature (Q 10 Ϸ 1.2) in mixtures with KaiA and KaiB, which is consistent with the in vivo rhythm in cyanobacterial gene expression. Interestingly, the ATPase activity of KaiC when incubated without KaiA and KaiB is almost constant across temperatures.…”
supporting
confidence: 50%
“…The activity of KaiC (15 ATP per day) is unusually low. Terauchi et al (5) hypothesize that ATP hydrolysis by KaiC induces conformational change in the KaiC hexamer, which may slow the rate of ATP hydrolysis, and they further speculate that this autoregulation may contribute to temperature compensation. Additional biophysical and structural analyses should enhance understanding of how intra-and intermolecular interactions affect ATPase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the circadian rhythm of KaiC phosphorylation persisted for at least 3 cycles after the rapid disappearance of kaiABC mRNA under continuous dark (DD) conditions even in the presence of excess transcription and translation inhibitors (2). More strikingly, incubating the 3 recombinant Kai proteins with ATP was sufficient to generate a temperature-compensated circadian KaiC phosphorylation cycle in vitro (3,4). Thus, the core process in generating basic oscillation is not a transcription/ translation feedback but is likely to be an enzymatic oscillation of KaiC phosphorylation/ATPase activities.…”
mentioning
confidence: 99%
“…Among these, studies on a prokaryotic model organism, cyanobacterium (Synechococcus elongatus PCC 7942), demonstrated that circadian oscillation of KaiC phosphorylation could be reconstituted in vitro by incubating the three Kai proteins and adenosine triphosphate (ATP) (3). Further studies have shown that an extremely weak but temperature-compensated ATPase activity of KaiC is tightly linked to the circadian period (4) and coupled to KaiC kinase/phosphatase activities to generate robust circadian oscillation (5). In cyanobacterial cells, time profiles of induction or repression of gene expression by KaiC match the circadian period (6).…”
mentioning
confidence: 99%